Frontline employees’ cognitive appraisals and well-being in the face of customer aggression in an Eastern, collectivist culture - Chuanchuen Akkawanitcha (2018)
© 2015, Emerald Group Publishing Limited. Purpose – This research aims to examine the cognitive appraisals of frontline employees (FLEs) when dealing with aggressive customers and the impact on their well-being, as well as several moderator effects, in a collectivist, Eastern culture. Design/methodology/approach – A critical incident technique reveals the cognitive appraisal of FLEs who had recently experienced customer aggression. Data were collected through qualitative, in-depth interviews with 35 FLEs in customer-facing roles in Thailand. Findings – The FLEs perceived threats to self-esteem, physical well-being, goal completion at work, fairness or equity and sense of control when dealing with customer aggression. These cognitive appraisals affected their psychological well-being in the form of negative affectivity, anxiety, depression and stress. Importantly, factors that moderate (exacerbate or weaken) the impact of customer aggression on cognitive appraisal, and cognitive appraisal on psychological well-being were revealed, including “customer is always right” philosophy, social status, public versus private context and social support. Practical implications – Organisations should pay more attention to FLEs’ psychological well-being and how they interpret and deal with customers’ misbehaviour and aggression. The research identifies factors that moderate the impact of customer aggression on psychological well-being. Originality/value – This is the first empirical paper that has examined how FLEs cope with customer aggression in a collectivist, south-east Asian context where social norms calibrate FLEs’ responses to customer aggression. It is also the first research that adopts a contingency approach to understanding how FLEs cope with customer aggression – i.e. when faced with customer aggression, under what contingency conditions do FLEs cognitive appraisals have a stronger or weaker impact on their psychological well-being?